Bouveret syndrome - Petracchi, Enrique; Chaktoura, Diego; Merchán, Pablo (Cirugía del Uruguay, 2020)
Bouveret syndrome. A 59-year-old woman, she consulted the emergency for generalized abdominal pain, accompanied by nausea and vomiting of 72 hours of evolution. On physical examination, he presented a soft, distended abdomen, without signs of peritonism. The computed tomography revealed gastric obstruction secondary to the impact of a stone in the duodenal bulb. Gastrotomy was performed with extraction of lithiasis at the duodenal level and at the vesicular level, a raffia was performed with separate stitches and drainage was placed. Bouveret's syndrome, caused by a stone, lodges in the bulb and causes gastric obstruction secondary to a cholecystoduodenal or choledochododenal fistula. It occurs between 1 and 3% of all cases of gallstone ileus, most often in women aged 70 to 75 years. Clinically it presents with epigastric pain, nausea and vomiting. Surgical treatment is an option and therapeutic behavior must be individualized for each patient.